Budget impact analysis of Jivi (damoctocog alfa pegol, Bay 94-9027) in severe hemophilia A in Japan. (1st January 2021) - Fujii, Teruhisa; Kidoguchi, Yuko; Takahashi, Noriko; Yu, Eric; Ainiwaer, Dilinuer; Byrne, Aidan
Abstract: Objective: Hemophilia A (HA) is a genetic bleeding disorder characterized by a deficiency of clotting factor VIII (FVIII) requiring lifelong prophylactic treatment typically with conventional standard half-life recombinant FVIII (rFVIII). Lifelong prophylaxis impacts budget, patient adherence, and long-term outcomes. The consequent economic and treatment burden may be reduced by using novel extended half-life rFVIII. The objective of this analysis was to estimate the budget impact of introducing Jivi (damoctocog alfa pegol, BAY 94-9027), hereafter referred to as BAY 94-9027, as an on-demand and prophylactic treatment for severe HA from a Japanese payer's perspective. Methods: A global budget impact model was adapted to the Japanese setting using data obtained via a targeted literature review of Japanese sources. The model considered a five-year time horizon for a market without and with BAY 94-9027. Using annual per-patient costs, the total cost of on-demand and prophylactic treatment of adolescent and adult patients with severe HA (without inhibitors) were analyzed. The model used summary of product characteristics (SmPC) and clinical trial dosing, and unit costs from the National Health Insurance (NHI) drug price database. Comparators considered in the model comprised of currently available products in Japan. Projected BAY 94-9027 uptake ranged from 4% to 9% over the five years (2020–2024). Results: Introduction of BAY 94-9027 for the treatment of severe HA is estimated to decrease the overall budget by 1.5%, with a cost saving of approximately $67 million USD (¥7.4 billion JPY) over five years. Estimated cost savings associated with BAY 94-9027 ranged from $1.4 million USD (¥156 million JPY) in 2020 to $23 million USD (¥2.6 billion JPY) in 2024 for the Japanese healthcare system. Limitations: There were limitations associated with the study. The Japanese guidelines consulted during the targeted literature review of national data sources in Japan were based on global data as reference sources. Also, studies reporting the bleeding rate, dosing guidelines, and economic burden in the Japanese population identified by the targeted literature review were limited hence global studies were used and may not have been representative of the Japanese population. Conclusions: BAY 94-9027 can reduce total severe HA treatment costs, driven by lower annual rFVIII utilization, and a narrow weekly dosing range compared to competitor products in the Japanese market.